The Implementation of Smart Cities in Indonesia: A Literature Study on Technology Based Governance and Public Services - Efendi, Erizal Candra; Yulia Ningsih (Universitas Bojonegoro, 2025)
The rapid development of Information and Communication Technology (ICT) has driven the implementation of Smart City initiatives in Indonesia as a solution to urban challenges such as congestion, pollution, inefficient governance, and inadequate public services. However, disparities in technological infrastructure and digital literacy remain significant obstacles to equitable Smart City development across regions. This study employs a qualitative research method with a literature review approach to analyze the implementation of Smart Cities in Indonesia. Data were collected from scientific journals, government reports, and case studies from both domestic and international Smart City initiatives. Thematic analysis was used to identify key patterns and trends in governance and technology-based public services. This research aims to explore the challenges, opportunities, and impacts of Smart City implementation in Indonesia, with a focus on governance efficiency and technology-driven public services. It also seeks to provide recommendations for optimizing Smart City strategies. The results indicate that major cities like Jakarta, Bandung, and Surabaya have successfully implemented Smart City frameworks, improving public service efficiency and government transparency. However, rural and small urban areas face challenges such as digital infrastructure gaps, low public engagement, and regulatory weaknesses in data protection and cybersecurity. Despite these challenges, the integration of Smart City technologies has the potential to enhance public participation, optimize resource management, and drive sustainable urban development. The study concludes that successful Smart City implementation in Indonesia requires (1) equitable access to digital infrastructure, (2) enhanced digital literacy programs, (3) strong data protection and cybersecurity regulations, and (4) effective collaboration between the government, private sector, and society. Addressing these aspects will enable Indonesia to develop Smart Cities that are inclusive, efficient, and sustainable for long-term urban transformation